CellFIE: CRISPR- and Cell Fusion-based Two-hybrid Interaction Mapping of Endogenous Proteins. Issue 24 (3rd December 2021) - Secker, Christopher; Kostova, Simona; Niederlechner, Hannah; Beetz, Stephanie; Wendland, Ina; Liebich, Mara J.; Polzer, Oliver; Groh, Mirjam; Schnoegl, Sigrid; Trepte, Philipp; Wanker, Erich E.
Graphical abstract: Highlights: Novel method for the detection of protein–protein interactions (PPIs) between endogenously tagged proteins. CellFIE utilizes fusion of haploid knock-in cell lines for mapping selected interaction pairs. CellFIE validates the endogenous interactions of VCP with UBXD1 and ASPL, and the self-interaction of TDP-43 in live cells. CellFIE sensitively quantifies changes on PPIs upon stress induction or drug treatment. Abstract: Numerous genetic methods facilitate the detection of binary protein–protein interactions (PPIs) by exogenous overexpression, which can lead to false results. Here, we describe CellFIE, a CRISPR- and cell fusion-based PPI detection method, which enables the mapping of interactions between endogenously tagged two-hybrid proteins. We demonstrate the specificity and reproducibility of CellFIE in a matrix mapping approach, validating the interactions of VCP with ASPL and UBXD1, and the self-interaction of TDP-43 under endogenous conditions. Furthermore, we show that CellFIE can be used to quantify changes of endogenous PPIs upon stress induction or drug treatment. For the first time, CellFIE facilitates systematic mapping of interactions between endogenously tagged proteins and represents a novel tool to characterize PPIs in live cells under dynamic conditions.